Factors Influencing Consumer Purchase Decisions: A Study on Pawon Klotok Ning Ninik Products in Surabaya: Faktor-faktor yang Mempengaruhi Keputusan Pembelian Konsumen: Sebuah Studi pada Produk Pawon Klotok Ning Ninik di Surabaya - Ghianti, Anneke Chitra; Sukmono, Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study investigates the impact of packaging, product quality, price, and brand on consumer purchasing decisions for Pawon Klotok Ning Ninik products in Surabaya. Employing non-probability accidental sampling, data from 97 consumers who purchased these products were analyzed using IBM SPSS Statistics version 22. The findings confirm that packaging, product quality, price, and brand individually influence purchasing decisions, and collectively, they significantly impact consumer choices. This research sheds light on the dynamics of consumer behavior in the context of food products and provides valuable insights for marketers and businesses seeking to enhance their market strategies. Highlights: The study explores factors influencing consumer purchase decisions. Pawon Klotok Ning Ninik products in Surabaya serve as the research context. Packaging, product quality, and brand significance in consumer choices are highlighted. Keywords: Consumer Purchase Decisions, Pawon Klotok Ning Ninik, Packaging, Product Quality, Brand Influence